A Review of Factors Related to Gender and Ethnic Differences in Math/Science Achievement Levels of Students K-12 - Iris Riggs (Educational Considerations, 1988)
The primary feature of successful programs for women and minorities seem to be that they involve the students in the "doing" of science and mathematics.